2021
DOI: 10.32598/ijmtfm.v11i3.34968
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Vitamin D Levels and the Severity of Anxiety and Depression in Patients Under Methadone Maintenance Treatment

Abstract: Background: Hypovitaminosis D, low bone mineral density, non-specific musculoskeletal pain, increased risk of fracture, and periodontal disease were reported in most subjects recruited from the Methadone Maintenance Treatment (MMT) program. This study aimed to determine the relationship between vitamin D levels and the severity of anxiety and depression in patients under MMT. Methods: In a cross-sectional study, serum vitamin D levels were measured among 500 patients under MMT from Kashan Province, Iran. Corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Low levels of this vitamin can also cause neuropsychiatric disorders such as depression, schizophrenia, Alzheimer's disease, and autism. In addition, epidemiological and clinical studies have demonstrated that individuals with low vitamin D levels are more vulnerable to depression (6,7). In the past, vitamin D was known as an anti-rickets agent or the sunshine vitamin.…”
Section: Introductionmentioning
confidence: 99%
“…Low levels of this vitamin can also cause neuropsychiatric disorders such as depression, schizophrenia, Alzheimer's disease, and autism. In addition, epidemiological and clinical studies have demonstrated that individuals with low vitamin D levels are more vulnerable to depression (6,7). In the past, vitamin D was known as an anti-rickets agent or the sunshine vitamin.…”
Section: Introductionmentioning
confidence: 99%